A Facile Route to Metal Oxides/Single-Walled Carbon Nanotube Macrofilm Nanocomposites for Energy Storage - Cao, Zeyuan; Wei, Bingqing (Frontiers in Materials, 2015)
Nanocomposites consisting of transition-metal oxides and carbon nanomaterials with a desired size and structure are highly demanded for high performance energy storage devices. Here, a facile two-step and cost-efficient approach relying on directly thermal treatment of chemical-vapor-deposition products is developed as a general synthetic method to prepare a family of metal oxides (MxOy (M=Fe, Co, Ni))/single-walled carbon nanotube (SWNT) macrofilm nanocomposites. The MxOy nanoparticles obtained are of 3-17 nm in diameter and homogeneously anchor on the free-standing SWNT macrofilms. NiO/SWNT also exhibits a high specific capacitance of 400 F g-1 and fast charge-transfer Faradaic redox reactions to achieve asymmetric supercapacitors with a high power and energy density. All MxOy/SWNT nanocomposites could deliver a high capacity beyond 1000 mAh g-1 and show excellent cycling stability for lithium-ion batteries. The impressive results demonstrate the promise for energy storage devices and the general approach may pave the way to synthesize other functional nanocomposites.